Investigation of the localized surface plasmon effect from Au nanoparticles in ZnO nanorods for enhancing the performance of polymer solar cells. Issue 2 (28th November 2014) - Ho, Yu-Che; Kao, Shao-Hsuan; Lee, Hsin-Che; Chang, Sheng-Kai; Lee, Cheng-Che; Lin, Ching-Fuh
Abstract : The organic polymer solar cell is recognized as one of the most competitive technologies of the next generation. Abstract : The organic polymer solar cell is recognized as one of the most competitive technologies of the next generation. Au nanoparticles and ZnO nanorods were combined to improve the inverted-structure low-bandgap polymer solar cells and enhance the absorption and efficiency of the devices. However, the Au nanoparticles tend to aggregate in solution, thus reducing the localized surface plasmon resonance (LSPR) effect. The cluster effect on the spectral range of enhancement in the absorption is investigated and the absorption characteristics of the LSPR receive proper modification through our experiment. After reducing the number of Au nanoparticle clusters, the LSPR effect in the devices was clearly verified. The proper combination of the Au nanoparticles and ZnO nanorods leads to the power conversion efficiency of the PTB7 : PC71 BM inverted organic solar cell reaching 8.04% after optimizing the process conditions.